Complement genes in black rockfish (Sebastods schlegelii): genome-wide identification, evolution and their potential functions in response to Vibrio anguillarum infection. Issue 114 (July 2021) - Li, Qi; Cao, Min; Fu, Qiang; Yang, Ning; Yan, Xu; Song, Lin; Li, Chao
Abstract: As complex components of innate immune system, members of complement system play crucial roles during the process of defensing against pathogens. Black rockfish ( Sebastes schlegelii ) is one of the important aquaculture species in East Asian. However, studies of complement genes in black rockfish and its related immune activities are still lacking. Therefore, a total of 112 members of the complement genes were identified from the genome of black rockfish and were classified into five subgroups. According to their functional annotations, 30 genes belonged to pattern recognition, 6 genes belonged to proteases, 14 genes belonged to complement components, 36 genes belonged to receptors, and 26 genes belonged to regulators. It can be found that many complement genes evolved into multi-copies, especially in teleost, which may be influenced by whole-genome duplication or tandem duplication events. Complement genes were randomly distributed on 22 chromosomes. The number of introns of complement genes varied from 1 to 70. Results of the expression patterns of 10 randomly selected genes from 5 subtypes response to Vibrio anguillarum infection revealed that most of the members of the complement genes were induced in gill and skin. In contrast, most genes in intestine showed downregulation. This study systematically characterized and analyzed the complement genes in black rockfish and provided new insights into their functions responding to bacterial infection. Highlights: A total of 112 complement genes were identified in black rockfish. According to function, 112 genes can be divided into five subtypes. It can be found that many complement genes evolved into multi-copies. Expression patterns of 10 selected genes response to  V. anguillarum  infection were investigated.